Sebaran Parameter Akustik Ikan Pelagis Kecil di Teluk Cenderawasih, Papua - Hisyam, Muhammad; Pujiyati, Sri (Cenderawasih University, 2024)
Cenderawasih Bay is one of the territorial waters of Indonesia which has a fairly high fishery potential. In 2022, the bay's fishery potential reaches 135,140 tons but the utilization rate is still at 0.3, which means that it has not been fully utilized, especially small pelagic fish. This shows the need for an estimation of the distribution of fish in the bay that can take advantage of the hydroacoustic method. This research uses a split beam echosounder SIMRAD EY-60 which is operated at a frequency of 38 KHz and a pulse duration of 1,024 ms to obtain fish distribution data. Environmental parameter data was obtained using data from marine.copernicous.eu at the same time as fish distribution data collection. The distribution of fish also shows a fairly diverse distribution of values with the highest SV value range at -59.7 to -57.4 dB and the highest TS range at -59.4 to -46.7 dB. The distribution of fish was also seen to be more concentrated in areas with warm temperatures and spread evenly in each salinity range with the number of fish detected approaching areas of higher chlorophyll concentration.